Pain Catastrophizing Is Related to Static Postural Control Impairment in Patients with Nonspecific Chronic Low Back Pain: A Cross-Sectional Study - Chanjuan Zhang; Zhou Zhang; Yuelong Li; Chenyang Feng; Haiqi Meng; Yang Gao; Wai Leung Ambrose Lo; Chuhuai Wang (Pain Research and Management)
Purpose. Pain catastrophizing may contribute to the altered trunk muscle activity in patients with nonspecific chronic low back pain (NSCLBP). It is unclear if pain catastrophizing influences static postural control in patients with NSCLBP. This study aimed to investigate the relationship between pain catastrophizing and static postural control in NSCLBP patients. Methods. Sixty-eight participants with NSCLBP and 40 healthy participants were recruited. Postural control was assessed by the sway area and the sway length of the center of pressure (COP) during balance tests. Pain catastrophizing in participants with NSCLBP was assessed by the Pain Catastrophizing Scale (PCS). Bilateral transversus abdominis (TrA) activation was evaluated by ultrasound imaging-measured percent change in muscle thickness. Associations between COP parameter and PCS/subscales of PCS were examined by multiple linear regression (MLR). Results. Our results observed a larger COP sway area in NSCLBP group under eyes-closed condition p<0.001 and a lower level of voluntary activation of the bilateral TrA p<0.001, compared with the healthy control group. The MLR analyses revealed that the COP area sway under eyes-closed condition was significantly associated with the PCS score/helplessness score of PCS, voluntary activation of the left TrA, and age in participants with NSCLBP (β = 0.222/0.236, 0.341/0.344, and 0.328/0.325; p=0.045/0.033, 0.002, and 0.004, resp.). Conclusions. Static postural control was associated with pain catastrophizing, voluntary activation of TrA, and age in participants with NSCLBP. This indicated that pain catastrophizing may affect postural control and should be considered when interpreting balance test results and managing NSCLBP.